2024
DOI: 10.1038/s41398-024-02771-9
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids, endocannabinoid-like compounds and cortisone in head hair of health care workers as markers of stress and resilience during the early COVID-19 pandemic

Ingeborg Biener,
Tonina T. Mueller,
Jin Lin
et al.

Abstract: The pandemic caused by SARS-CoV-2 impacted health systems globally, creating increased workload and mental stress upon health care workers (HCW). During the first pandemic wave (March to May 2020) in southern Germany, we investigated the impact of stress and the resilience to stress in HCW by measuring changes in hair concentrations of endocannabinoids, endocannabinoid-like compounds and cortisone. HCW (n = 178) recruited from multiple occupation and worksites in the LMU-University-Hospital in Munich were inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Initial research employing hair ECs/NAEs found reduced hair OEA levels in rebel war survivors with versus without PTSD as well as negative associations of hair NAE levels with number of traumatic events and PTSD symptom severity, respectively (Wilker et al, 2016). In community samples, hair EC/NAE levels were also negatively associated with burnout and anxiety symptoms (AEA; Gao et al, 2020), childbirth-related PTSD symptoms (AEA; Bergunde et al, 2023), and depressive symptoms (AEA; Walther et al, 2023) and reduced in health-care workers with anxiety (SEA and PEA; Biener et al, 2024), supporting an EC/NAE deficiency hypothesis in stress-related psychopathology. However, some studies found positive or no associations between hair ECs/NAEs and trauma and PTSD, or depressive, and anxiety symptoms (e.g., Behnke et al, 2021Behnke et al, , 2021Croissant et al, 2020), highlighting the need for further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Initial research employing hair ECs/NAEs found reduced hair OEA levels in rebel war survivors with versus without PTSD as well as negative associations of hair NAE levels with number of traumatic events and PTSD symptom severity, respectively (Wilker et al, 2016). In community samples, hair EC/NAE levels were also negatively associated with burnout and anxiety symptoms (AEA; Gao et al, 2020), childbirth-related PTSD symptoms (AEA; Bergunde et al, 2023), and depressive symptoms (AEA; Walther et al, 2023) and reduced in health-care workers with anxiety (SEA and PEA; Biener et al, 2024), supporting an EC/NAE deficiency hypothesis in stress-related psychopathology. However, some studies found positive or no associations between hair ECs/NAEs and trauma and PTSD, or depressive, and anxiety symptoms (e.g., Behnke et al, 2021Behnke et al, , 2021Croissant et al, 2020), highlighting the need for further clarification.…”
Section: Introductionmentioning
confidence: 99%